2007
DOI: 10.1111/j.1464-410x.2007.06917.x
|View full text |Cite
|
Sign up to set email alerts
|

Organ‐sparing surgery does not lead to greater antisperm antibody levels than orchidectomy

Abstract: From these data, organ-sparing surgery does not lead to greater ASA levels than orchidectomy and patients are therefore at no greater risk of developing an autoimmune infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…In a recent study, the anti-sperm antibody level between orchidectomy and OSS was not statistically significant. 15 The present study also showed that patients with OSS have stable semen quality compared with their preoperative levels. Our data demonstrate that OSS can effectively preserve the functional integrity of the testis.…”
Section: Discussionsupporting
confidence: 53%
“…In a recent study, the anti-sperm antibody level between orchidectomy and OSS was not statistically significant. 15 The present study also showed that patients with OSS have stable semen quality compared with their preoperative levels. Our data demonstrate that OSS can effectively preserve the functional integrity of the testis.…”
Section: Discussionsupporting
confidence: 53%
“…While inguinal orchidectomy remains the standard for the diagnosis and staging of testicular neoplasms, we believe that removal of a testis for a benign lesion should be avoided. Organ-sparing surgery for benign lesions has been widely accepted and is widely advocated for the treatment of even malignant and stromal tumours [15,[29][30][31][32][33]. The use of frozen section examination is recommended, particularly in small tumours.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it is clear that ASA-associated infertility is not absolute but depends on concentration, avidity, biological activity, and the antibodies' Ig class. It should also be stressed that Guazzieri et al (19) used immunofluorescence and immunoenzymatic assays, which can give numerous false-positive and falsenegative results and are therefore not considered as reference methods. Furthermore, the numerous studies of ASA demonstrate that the results achieved with radioimmunologic and immunoenzymatic methods are characterized by a low sensitivity and specificity, owing to the use of extractive antigens (21,22).…”
Section: Discussionmentioning
confidence: 98%